MicroCT-Based Methodology for Defect Detection and Analysis in GRFP Tube Joints - Cintia Ferreira; Olga M. O. Araújo; Alessandra Silveira Machado; Davi F. Oliveira; Gabriela Ribeiro Pereira; Ricardo Tadeu Lopes (e-Journal of Nondestructive Testing)
Composite materials are created by combining different substances, each contributing specific properties that enhance the material's overall performance. Given the diversity of composite types, a range of Non-Destructive Testing (NDT) techniques has been developed for their inspection, each offering unique benefits. Among these, Computed Microtomography (micro-CT) emerges as a particularly powerful method for volumetric analysis, providing highly detailed three-dimensional (3D) imaging of internal structures. This study aims to develop a methodology for analyzing the joints of polymer composite tubes. To achieve this, the volumes of the matrix, reinforcement, and any defects within the selected samples were meticulously evaluated. The findings reveal that the micro-CT technique, when integrated with advanced image processing tools, is highly effective for detecting, locating, and quantifying defects.